1963
DOI: 10.1083/jcb.19.3.551
|View full text |Cite
|
Sign up to set email alerts
|

ULTRASTRUCTURAL STUDIES ON THE BLUE-GREEN ALGAL SYMBIONT IN CYANOPHORA PARADOXA KORSCHIKOFF

Abstract: Studies conducted on the ultrastructurc of Cyanophora paradoxa Korschikoff (a cryptomonad) have shown that its intracellular symbiont is closely related to unicellular blue-green algae. Due to its peculiar habitat, the intracellular symbiont lacks the characteristic cyanophyccan double-layered cell wall, but is surrounded by a thin protoplasmic membrane. The protoplasm itself is differentiated into a lamellated chromatoplasm containing photosynthetic pigments, polyphosphate granules, and possible oil drople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
2

Year Published

1967
1967
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(50 citation statements)
references
References 5 publications
1
47
2
Order By: Relevance
“…Cyanophora paradoxa is a glaucophyte biflagellate assumed to have the most primitive features among the photosynthetic eukaryotes (Hall and Claus 1963, Mignot et al 1969, Spiegel 2012. This alga has been examined extensively as a model organism of primitive phototrophs (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanophora paradoxa is a glaucophyte biflagellate assumed to have the most primitive features among the photosynthetic eukaryotes (Hall and Claus 1963, Mignot et al 1969, Spiegel 2012. This alga has been examined extensively as a model organism of primitive phototrophs (e.g.…”
mentioning
confidence: 99%
“…Sato et al 2005, Watanabe et al 2009, Frassanito et al 2010, Leblond et al 2010, Facchinelli et al 2013. Ultrastructural features of C. paradoxa were examined using transmission and scanning electron microscopy (TEM and SEM, respectively) to demonstrate that the cell periphery lacks a cell wall but consists of plasma membrane and flattened vesicles containing a plate just underneath the membrane (Hall and Claus 1963, Mignot et al 1969, Trench et al 1978, Kies 1979, Kugrens et al 1999. Using conventional SEM, Kugrens et al (1999) examined two species of Cyanophora.…”
mentioning
confidence: 99%
“…In the atypical case of Gloeobacter violaceus, the phycobilisomes are attached to the plasma membrane (15). The cyanelles of Cyanophora paradoxa are generally regarded as cyanobacterial endosymbionts within a flagellated unicellular eukaryote (16,30,34). According to the endosymbiotic theory of the origin of chloroplasts, associations such as that found in Cyanophora could have been an intermediate step in the evolution of red algal chloroplasts (24,25,32).…”
mentioning
confidence: 99%
“…Authors of seminal studies described the glaucophyte plastids as "protoplasm colored bodies", "endosymbiotic blue-green photosynthesizing prokaryotes", "prokaryotic blue-green endocytobionts" or "endocyanomes". Some of these studies even described the blue-green plastids as cyanobacterial species [54] and highlighted their "intermediate" characteristics between free-living cells and organelles [55,56]. Further molecular studies demonstrated that the glaucophyte blue-green "bodies" are photosynthetic organelles [57][58][59].…”
Section: The Defining Characteristics Of Glaucophytamentioning
confidence: 99%
“…2) [54,60]. These latter two traits are considered plesiomorphic characters for Archaeplastida that have been uniquely retained in glaucophytes (extended descriptions of these two traits are provided in the section "The blue-green plastids of glaucophytes" below).…”
Section: The Defining Characteristics Of Glaucophytamentioning
confidence: 99%